DEVELOPMENT OF GOLD NANOPARTICLE-BASED COLORIMETRIC 3âUTR APTASENSOR FOR RNA SARS-COV-2 DETECTION - Verdiani, Hana
Detection is one of the keys to controlling the spread of the virus in the condition of the COVID-19 Pandemic. Gold nanoparticle-based colorimetry aptasensor are widely used as nanosensor devices because the simplicity of the detection, very sensitive in detecting target molecules. Apatmer used in this study, was developed to detect the presence of SARS-CoV-2 RNA analyte. Aptamer binds to the target RNA, causing nanoparticles aggregation under high salt conditions, and characterized by a discoloration of the solution of the nanoparticles that were originally red to purple. The development of this aptasensor has promising potential and can be utilized as an alternative to countering extraordinary events such pandemic in the future. This research aims to develop a gold nanoparticle-based sensor colorimetry with an aptamer designed from conserved area of the SARS-CoV-2 genome to detect the presence of SARS-CoV-2 RNA analytes. In general, the research flow is divided into two main stages, in silico analysis and wet lab experiments. In silico analysis is performed by designing aptamer sequence from 3' UTR area of SARS-CoV-2 genome, performing secondary and tertiary structural analysis, and analysis of the aptamer-target interaction. In this study, raw materials used were 5 nm AuNP Sigma Aldrich (n=3), NaCl (0-7M) solution, aptamer solution (0-5 uM), positive control (conserved sequence of 3'UTR), negative control (NFW solution), and sample (RNA extracted). The intensity of the discoloration in the solution is measured using a UV-Vis spectrophotometer. The designed aptamer can form a stable bond to the target based on modeling interaction with molecular docking with free energy binding value of 51.6 Kcal/mol. The detection limit of aptasensor colorimetry was 22.46 ng/uL, which was obtained after successfully optimizing the test conditions for aptamer concentration (1uM), AuNP volume (350 uL), NaCl concentration (5 M) and aptamer-target incubation time (60 minutes). This study successfully developed a colorimetric aptasensor that can detect the presence of SARS-CoV-2 RNA analytes in the range of CT 11.22 - 30.9.